Rural Roads and Local Economic Development - Asher, Sam; Novosad, Paul (World Bank, Washington, DC, 2018)
Nearly one billion people worldwide live in rural areas without access to the paved road network. This paper measures the impacts of India's $40 billion national rural road construction program using regression discontinuity and data covering every individual and firm in rural India. The main effect of new feeder roads is to allow workers to obtain nonfarm work. However, there are no major changes in consumption, assets or agricultural outcomes. Nonfarm employment in the village expands only slightly, suggesting the new work is found outside of the village. Even with better market connections, remote areas may continue to lack economic opportunities.